Online Learning Management in The Covid-19 Pandemic Era - Herry Sanoto (JETL (Journal of Education, Teaching and Learning), 2021)
Learning in the era of the Covid-19 pandemic has undergone a fundamental change from a face-to-face learning process to online-based learning to minimize the transmission of the Covid-19 virus. Online learning is basically a learning model with internet technology media, so that the learning process can be carried out even though it is in different places. The research method in this research is qualitative research by describing the online learning management process that is carried out at SMP LAB UKSW. The instruments in this research include observation sheets, student opinion questionnaires, and interview guides. The results showed that the online learning process applies management principles which include planning, organizing, implementing and controlling. The results of student and teacher opinions show that online learning has a positive perception of 83%. The results of the interview showed that the students felt that they were well facilitated by the online learning process that was conducted at SMP LAB UKSW.